Feuilleton loves, contributions of social constructionism - Galindo, Dolores [UNESP]; Souza, Leonardo Lemos de [UNESP] (Univ Autonoma Barcelona, Dept Psicologia Salut, 2017)
Love has been the subject of study of critical perspectives that seek the reconstruction of categories, ratings and generalizing standards in daily life. To problematize the love device, we seek dialogue with constructionist studies and feminist epistemologies having Folhetim literature as an analysis material. For this, we analyzed poetical short stories, focusing on female characters, published in the early twentieth century. The analysis considered three areas: (1) the narrative spaces that give the tensions between public and private; (2) the characters for which we inquire about the feminine and masculine characteristics, we seek entanglements between emancipation and social practices of the time and (3) images of love that crossed the different tales. We entertained the idea that this genre of literature puts into circulation modes of subjectivity loves producing areas and modulating modes of existence of the uses of public and private spaces, and gender relations in daily life.
Keywords: Love; Feuilleton; Gender; Social Construcionism